Interferon Treatment of Multiple Pulmonary Malignancies Associated with Papilloma Virus. Issue 6 (3rd September 2004) - Aaron, SL; Wong, E; Tyrrell, D; Duggan, M; Vallieres, E; Jewell, L; Romanowski, B
Abstract : Over a period of four years, beginning in spring 1988, a previously healthy man developed a primary squamous cell carcinoma of the tonsil, treated with radiotherapy, followed by 10 distinct, primary bronchial squamous cell carcinomas. Four of the cancers were surgically resected, all of which were positive by hybridization for human papilloma virus (type 16). Following the institution of alpha interferon, three smaller lesions disappeared and a larger one shrank in size, facilitating surgical resection. Over the following seven years no new ones have appeared. The finding of papilloma virus in malignancies should prompt consideration of antiviral therapy.